Delivering Resilience : Embedding a Resilience Building Module into First-Year Curriculum. - Goodchild, Tracy; Heath, Georgina; Richardson, Amanda (Student Success v.14 n.2 p.30-40 https://doi.org/10.5204/ssj.2883, 2023)
Starting university is challenging. Students require resilience to face the inevitable challenges of university life, yet many may not be equipped with the strategies they need. In this research, we explored changes in resilience following the delivery of a resilience building module within a core first-year university course. Psychology students at the University of South Australia completed the adapted Resilience at Work Scale at two separate time points and undertook a resilience building module. Pre- and post-scores were obtained for students' resilience (n = 205; n = 100 respectively); overall and components. On average, students had good levels of resilience at commencement, yet scores increased significantly across most components following completion of the module. Additionally, students who reported implementing resilience strategies experienced significantly higher score increases than their peers who did not. These findings hold important implications for staff across universities in relation to embedding resilience building programs into curriculum. [Author abstract]